(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
يهدف هذا العمل لدراسة بعض خصائص الفضاء المتراصّ من النّوع ( compact space ) ، والعلاقة بينه وبين أنواع أخرى من التراصّ ، و دراسة الفضاء ( ولانسكي)، وذلك بالاعتماد على مفهوم المجموعة المفتوحة من النّوع الذي وضع من قبل الباحث الرّياضي Njastad عام 1965, ولقد توصّلنا إلى بعض النتائج منها : كلّ فضاء متراصّ بقوّة هو فضاء متراصّ لكنّ العكس غير صحيح بالضرورة , كلّ فضاء هو فضاء . In this work we studied some properties of type compact space and the relationship between it and the other types of compactness and studied space by relying on the notion of open set was developed by mathematician Njastad in 1965, and we had reached some results such as : Every strongly compact space is compact space but the opposite is not necessarily true . Every space is space.